2017
DOI: 10.1523/jneurosci.3648-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Two Components of Aversive Memory inDrosophila, Anesthesia-Sensitive and Anesthesia-Resistant Memory, Require Distinct Domains Within the Rgk1 Small GTPase

Abstract: Multiple components have been identified that exhibit different stabilities for aversive olfactory memory in Drosophila. These components have been defined by behavioral and genetic studies and genes specifically required for a specific component have also been identified. Intermediate-term memory generated after single cycle conditioning is divided into anesthesia-sensitive memory (ASM) and anesthesia-resistant memory (ARM), with the latter being more stable. We determined that the ASM and ARM pathways conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 114 publications
1
2
0
Order By: Relevance
“…We previously showed that genes tagged with GFSTF faithfully reproduce the expression and subcellular distribution pattern of all tagged proteins tested ( Nagarkar-Jaiswal et al, 2015b ). We confirmed this observation as the similarities between GFSTF localization ( Figure 1—figure supplement 1 ) and published antibody staining for Cactus ( Zhou et al, 2015 ), Rgk1 ( Murakami et al, 2017 ), Discs large 1, and Bruchpilot ( Nagarkar-Jaiswal et al, 2015b ) in the brain are obvious. However, GAL4 strongly amplifies the expression of UAS-mCD8::GFP when compared to the endogenous GFP tagged proteins but the subcellular protein distribution is lost.…”
Section: Resultssupporting
confidence: 80%
“…We previously showed that genes tagged with GFSTF faithfully reproduce the expression and subcellular distribution pattern of all tagged proteins tested ( Nagarkar-Jaiswal et al, 2015b ). We confirmed this observation as the similarities between GFSTF localization ( Figure 1—figure supplement 1 ) and published antibody staining for Cactus ( Zhou et al, 2015 ), Rgk1 ( Murakami et al, 2017 ), Discs large 1, and Bruchpilot ( Nagarkar-Jaiswal et al, 2015b ) in the brain are obvious. However, GAL4 strongly amplifies the expression of UAS-mCD8::GFP when compared to the endogenous GFP tagged proteins but the subcellular protein distribution is lost.…”
Section: Resultssupporting
confidence: 80%
“…Kenyon cells receive dopaminergic input, and acute exposure to cocaine results in altered expression of Ddc, which encodes Dopa decarboxylase, and down-regulation of Dop2R, which encodes a dopamine receptor in C11 in females (Supplemental Table S8). slo, which regulates neurotransmitter release at synapses (Jepson et al 2014), is up-regulated in response to cocaine, as is Rgk1, which plays a role in negative regulation of calcium channel activity (Murakami et al 2017). Down-regulation of jdp can lead to dopamine blockade through its activity as a cochaperone in synaptic vesicle release (Ye et al 2004).…”
Section: Cocaine-modulated Gene Expression In the Mushroom Bodiesmentioning
confidence: 99%
“…as distinct molecular and cellular mechanisms (Comas et al, 2004;Blum et al, 2009;Pagani et al, 2009;Aso et al, 2012;Bouzaiane et al, 2015;Murakami et al, 2017). rut mutants are impaired in specific memory phases (Tully and Quinn, 1985;Han et al, 1992;Blum et al, 2009;Scheunemann et al, 2013), including short-term memory (STM), encoded in γ KC, and MTM encoded in α/β KC (Scheunemann et al, 2013, Bouzaiane et al, 2015.…”
Section: Discussionmentioning
confidence: 99%